Forecasting Analysis on Land Detection System Based on Geographic Information System - Warnia Nengsih (IJITEE (International Journal of Information Technology and Electrical Engineering), 2018)
Geographic Information System (GIS) is an information system that performs geographic-based data visualization. The system performs mapping between various data points based on geographical location. Difficulties in mapping land in a region is the basis for the development of GIS applications for the detection of land. This system does not only detect vacant land in a region, but it also provides identification of land, and provides information about the size of the land, the land position, as well as access to nearby public facilities. The system is developed using a mobile platform as a value system that is more flexible and dynamic. For the analysis of the forecasting in an area uses a multiple regression method involving three independent variables, namely the use of dry land, the use of building land and land use. The results of the predictive forecasting provides location points of interest and public facilities located in the location which make it easy to give consideration in selecting a location which is appropriate to build.